ENGAGEMENTS AND ENTANGLEMENTS: THE CONTEMPORARY WAQF AND THE FRAGILITY OF SHI'I QUIETISM - Hamoudi, Haider Ala (The Journal of law and religion, 2020)
Two primary impulses have historically motivated the Iraqi Shi'i juristic establishment in its relations with the Iraqi state. The first, deeply embedded in centuries of Islamic jurisprudence, is to achieve maximum autonomy for the Shi'i community from the state. The second has developed more recently in response to the modern state's efforts to extend its hegemonic control over areas that premodern empires were content either to leave to the jurists to administer or at least to share the administration of with jurists. This is to have the state recognize and implement Shi'i rules within parts of the state infrastructure that are of core interest to the juristic establishment. There is an obvious tension between these two desires, nowhere more evident than in the subject of this article—namely, the law pertaining to the creation, management, and liquidation of the Islamic charitable land trust known as the waqf. On the one hand, Article 43 of Iraq's constitution declares the followers of religions and sects to be “free” in administering the waqfs and their affairs, suggesting a strong desire for autonomy and separation from state control. Yet the implementing legislation for this provision extends the existence of a thick state bureaucracy and hands its administration over to juristic authorities. The ultimate irony of this arrangement is that it subjects juristic forces to far more potential interference as a legal matter than they have ever been subjected to, even during the totalitarian rule of the Ba'ath. In the end, a religious establishment historically deeply suspicious of political rulers and political engagement—indeed, one that defines itself by virtue of its separation from the state—now finds itself deeply and dangerously entangled in state political and administrative affairs. This article explores how this came to be and some of the significant consequences that arise from it.